Dalle spiaggie latine alla Real Lisbona Relações culturais e transferências entre Roma e Lisboa no século XVIII - Diez del Corral Corredoira, Pilar (Biblioteca - Estudos & Colóquios, 2022)
This book presents one of the most prolific periods of Portuguese-Italian artistic and cultural relations, the 18th century. Through ten articles, which approach the subject from various angles such as literature, medals, painting, textiles, music, architecture, etc., a good sample of the close ties that unite Rome with the westernmost capital of Europe. A veritable round trip in which Roman models and taste are intermingled with the Portuguese protagonists who made this process of exchange between the former Papal States and the other great overseas Iberian empire.